HUBUNGAN ISLAM DENGAN KRISTEN (BARAT) DALAM SEJARAH - Miswar, Andi (RIHLAH, 2013)
Since classical times, until the middle and modern century, Muslim has been building relationships and communication with various centers of civilization and science in the world (including the West) to achieve greatness. Nevertheless, Islam has also gave a great contribution to the advancement of Europe and the West. Relations between the two communities often arise because of hatred and hostility respectively fanaticism. History proves that from the beginning, the west has shown hostility towards Islam both as a religion or as a public entity that has a different culture and civilization with them. Some Moslem also addressing them negatively and positively that the west can give a positive value to the Islamic civilization. Therefore, a wareness and dialogue among both civilizations are needed to maintain the harmony relationships.